Two constructions of new error-correcting pooling designs from orthogonal spaces over a finite field of characteristic 2 - Li, Zengti; Gao, Suogang; Du, Hongjie; Zou, Feng; Wu, Weili (Journal of combinatorial optimization, 2010)
In this paper, we construct two classes of t × n , s e -disjunct matrix with subspaces in orthogonal space of characteristic 2 and exhibit their disjunct properties. We also prove that the test efficiency t / n of constructions II is smaller than that of D’yachkov et al. (J. Comput. Biol. 12:1129–1136, 2005 ).